Physicochemical parameters of the gum of Terminalia catappa L. (almendrón). - Martínez, Maritza; Vera, Antonio; Parra, Juan; Beltrán, Olga; Leal, María Gabriela; Le Cerf, Didier; Picton, Luc (Ciencia, 1970)
In Venezuela, the genus Terminalia (Combretaceae), is represented by thirteen (13) species. Terminalia catappa exudes an amber-colored gum, soluble in water. Relatively few studies exist concerning the gum of this species. The objective of this work is to determine the physicochemical parameters of the gum of T. catappa and to compare these parameters to those published for other gum exudates of Combretaceae. The physicochemical parameters were determined by the classic methodology for carbohydrates, size exclusion chromatography SEC-MALLS and IR spectroscopy. In general, the gum of T. catappa showed parameters comparable to those reported for the species of the same genus and, in general, of the sub-tribe Terminaliinae. It also exhibits characteristics analogous to those exudates from Combretumspp. (sub-tribe Combretinae). Greater differences were observed withthe gum of Laguncularia racemosa, belonging to a superior taxonomic category (Tribe Laguncularieae). The physicochemical parameters constitute an important fingerprint in order to differentiate gums of diverse species and genus. The gum of T. catappa exhibits properties which confer it a potential technological interest.